EDUCATED UNEMPLOYMENT AND READINESS OF INDONESIA IN ENTERING THE SINGLE MARKET OF ASEAN ECONOMIC COMMUNITY (Universitas Negeri Semarang, 2015)
The unemployment in Indonesia is high and it continues to threaten the world. Several factors which cause the educated unemployment are: (1) curriculum plan cannot be fully implemented as an actual curriculum; (2) curriculum focuses more on the hard skills and less on soft skills development. From the preliminary research stage (method R & D), the factual implementation of curriculum management was obtained. The subjects were chairman of the Program, lecturers, and students from thepurposively selected object. Data collection techniques were observation and interview guidelines. The validity of the data used triangulation instruments and resources. The data were analyzed using interactive analysis techniques through data collection, data reduction, data presentation, and conclusion. The results obtain: (1) management curriculum has been implemented using the four functions of management, and the result is not optimal yet, (2) it has not been fully based on CBC and KKNI, (3) there is limited time to evaluate the implementation and action in the curriculum management, (4) it has not been fully oriented to the development of soft skills and SCL, (5) there is balance between hard skills and soft skills and it has someprogrammed extracurricular activities, (6) there is nolearningimplementation and thedesigned SKL is in accordance with SKK. In conclusion, the educated unemployment and the readiness of Indonesia to enter the single market of MEA 2015 can be done through: (1) curriculum managementdevelopment and soft skills of students, (2) creating appropriate interrelation between SKL with SKK. In order to achieve both goals, conducting concrete steps are necessary.